Digital Competitiveness of Tourism SMEs - et. al., Guan Xin, Guo Hui, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research examines the digital competitiveness of tourism SMEs in Thailand in hosting Chinese inbound tourists through their websites. Integration of tourism-related technology and social media funnels were considered as significant factors of analysis. Twenty-five tourism companies' online content, including their websites, social media contents, and digital publications, were analyzed to conclude the study results. Though most of the large tourism service providers such as hotels and airline companies have been working on bypassing the travel agency commission charges through direct selling with digital platforms, most of the tourism SMEs in Thailand still depend on third-party agents for hosting their services. The results reveal that Thailand - China tourism business is either B2B or B2B2C or even B2B2B2C models. A very limited number of companies with B2C models can directly reach and host the inbound Chinese tourism market. This research's findings are threefold - a methodology for assessing the digital destination hosting patterns, digital content analysis of tourism SMEs, and determining the business models through the website. Further research directions in this domain were also proposed.